EFEKTIFITAS PENGGUNAAN PAKU DAN SEKRUP PADA PAPAN BLOK BERBASIS INTI KOMPOSIT PARTIKEL KAYU KELAPA SAWIT - Indra Mawardi; - Hanif; - Ramli (Jurnal Teknologi, 2014)
Blockboard  for industrial furniture is not only enough to meet mechanical properties, but also ease the  forming process. The use of nails and screw was determined in the process of forming blockboard. The purpose of this research is to study the effectiveness of using  nails and screw on blockboard that uses the core palm oil wood particles. This research is expected later on benefics to the furniture industry  in using the appropriate nails and screw to the blockboard using the core palm oil wood particles. The nails and screw with a different diameter was used in the test of blockboard. Nailers is used specifically to wood and nails concrete, with 50 mm long  and  2,5 and 3 mm diameter. The results showed the positive and negative effectiveness of using nailers on  the core. The used of screw on both surface and core of the blokboard showed the positive result. The smaller diameter nailers used  the more effective will be on the core